Implementation of Digital Pixel Sensor Based Parallel Architecture For Automatic Braking System in Automobiles (International Journal of Engineering and Computer Science, 2015)
While automobiles moving on the road, if a pedestrian or an animal or anything commits to come on to the road unintentionally, then their motion features will be extracted, by which the automatic braking system of the automobile will be activated. Row-Parallel Processing of the input image achieves directional edge filtering and essential motion features are extracted with the Pixel-Parallel Processing based on the Digital Pixel Sensor(DPS) Technology